Dynamic of Pondok Pesantren as Indegenous Islamic Education Centre In Indonesia - Dihyatun Masqon (TSAQAFAH, 2011)
In Indonesia pesantren is known as the indigenous religious educational institution. The basic elements of pondok pesantren are: Kiai as a central figure, santri as a student who persues knowledge, pondok as dormitory where santri lives, and mosque which constitutes at the centre of educational activities. In general, due to the system and method of teaching, pondok pesantren classified into two kinds; traditional and modern. Never the less they are having the same vision and mission, that is to say that education is pondok pesantren is community oriented education by cultivating values, moral attitude, and character building of muslim community. That is the main reason that life atmosphere inside pesantren is in inspired strongly by what so called Panca Jiwa – Five Spirits – namely; sincerity, simplicity, self-reliance, Islamic brotherhood, and accountable freedom. In modern Indonesia today the expectation towards the role ofpesantren move on since early twentieth century, it is not only performing it’s three traditional roles as locus for transforming religious education, preserving muslim traditions, and producing scholars, but nowadays it plays an important role to educate and prepare leaders of tomorrow who posses specific qualities.